Effect of Saffron (Crocus sativus L.), as a Bioenhancer, on Pharmacokinetic of Acetaminophen: An Animal Study - Seyede Nargess Sadati Lamardi; Mohammad Reza Shams Ardekani; Katayoon Mireskandari; Mohammad Sharifzadeh; Maryam Yakhchali; Sima Sadrai (Tehran University of Medical Sciences, 2023)
In Traditional Persian Medicine (TPM) saffron is used as an accompaniment agent "Mobadreq" in poly herbal formulations. According to TPM texts, "Mobadreq" is a substance (or drug) which facilitates access of drugs or food to the whole body or specific organs. This study investigated the effect of oral co-administration of Crocus sativus L. (saffron) on the absorption and some pharmacokinetic parameters of acetaminophen in rats. Two groups of Rats (n=6) were treated by 1: acetaminophen 10 mg/kg along with Crocus sativus 4 mg/kg (test group) and 2: 10 mg/kg acetaminophen (control). The plasma concentrations of acetaminophen after oral administration (at 0, 5, 10, 15, 20, 40, 60, 90, and 120 min) were monitored by an HPLC-UV method. Results indicated that the plasma concentration of acetaminophen in the test group was reached to the maximum concentration (Cmax) faster than control group. As a result, at 5 to 40 minutes after drug gavage, the concentration of acetaminophen in both groups was significantly different.  It was also found that co-administration of acetaminophen and saffron significantly increased acetaminophen's area under concentration curve (AUC0-60) in compare to the acetaminophen alone (p<0.025). These results suggested that saffron could increase absorption rate of acetaminophen. Consequently, saffron can be considered and introduced as an enhancer of absorption rate and efficacy of acetaminophen and other drugs at least by oral route although the drug interactions with this herb should be considered.